Hydration status assessment techniques and their applicability among Olympic combat sports athletes: Literature review - Zubac, D.; Marusic, U.; Karnincic, H. (Strength and Conditioning Journal, 2016)
It is generally accepted that voluntary weight cutting before entering a competition has become a habitual practice among combat sports athletes. Apart from antidoping regulations banning the use of diuretics, the Olympic governing body has not established policies aimed to monitor aggressive weight cutting. It is extremely important for combat sports athletes to reduce adverse and health-threatening side effects evoked by different approaches to achieving competition weight. Therefore, development and implementation of reliable and accurate hydration assessment tools are warranted. The objective of this article is to review current research findings of measurement characteristics currently deployed in combat sports research.